Democratizing Data-Driven Agriculture Using Affordable Hardware - Chandra, Ranveer; Manohar, Swami; Chakraborty, Tusher; Ding, Jian; Kapetanovic, Zerina; Kumar, Peeyush; Vasisht, Deepak (IEEE Micro, 2022)
The world needs to sustainably grow more food to feed the growing population of the planet. Data-driven agriculture is a promising technique that can help farmers be more productive, reduce costs, and enable adoption of sustainable agricultural practices. However, the adoption of data-driven agriculture is limited by a lack of affordable technologies, for broadband, sensing, imaging, and insights. In this article, we present an overview of Project FarmBeats, a research project that started in 2014 to increase the adoption of data-driven agricultural practices. We provide an overview of the various components of the FarmBeats architecture, and details of the hardware innovations.